1989
DOI: 10.1111/j.1469-8986.1989.tb01917.x
|View full text |Cite
|
Sign up to set email alerts
|

Premenopausal and Postmenopausal Women Differ in their Cardiovascular and Neuroendocrine Responses to Behavioral Stressors

Abstract: Middle-aged (45-51 years) women performed four tasks while their heart rate, blood pressure, and plasma catecholamines were measured. The tasks were serial subtraction, mirror image tracing, speech, and postural tilt. The speech task was considered to be particularly relevant to women because of its emphasis on social skills. Fifteen premenopausal women reported menstruating regularly and were tested in the early follicular phase. Sixteen postmenopausal women reported not menstruating for at least 12 months an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
1
6

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(127 citation statements)
references
References 45 publications
9
111
1
6
Order By: Relevance
“…PMW appear to show greater sensitivity than premenopausal women in their physiologic response to cognitive and speech tasks with the difference being ascribed to both age and hormonal status (Saab et al, 1989). Previous studies of the effects of hormones on various forms of experimental stressors have found that the various forms of estrogen appear to reduce some of the physiologic effects of mild laboratory-induced stress (eg, solving arithmetic problems) (Ceresini et al, 2000).…”
Section: Stress Sensitivity Of Pmwmentioning
confidence: 99%
“…PMW appear to show greater sensitivity than premenopausal women in their physiologic response to cognitive and speech tasks with the difference being ascribed to both age and hormonal status (Saab et al, 1989). Previous studies of the effects of hormones on various forms of experimental stressors have found that the various forms of estrogen appear to reduce some of the physiologic effects of mild laboratory-induced stress (eg, solving arithmetic problems) (Ceresini et al, 2000).…”
Section: Stress Sensitivity Of Pmwmentioning
confidence: 99%
“…One subgroup of recruits (TSST-G-2 nd -defence) was asked to imagine that they were falsely accused of shoplifting a belt and were required to make a speech in their defence (Saab et al, 1989;Burleson et al, 2003). The other subgroup (TSST-G-2 nd -presentation) was given a short article about domestic politics, foreign policy, or economics and told that they would have two minutes to read the articles and prepare a speech about the given topic (adapted , 1997).…”
Section: Stress Provocationmentioning
confidence: 99%
“…To avoid participants presenting a memorized speech or remembering the sequence of correct responses to the mental arithmetic task on the second assessment session, different adaptations of the TSST subtasks have been used in the past: While during the first exposure, the original protocol of the TSST (Kirschbaum et al, 1993) is often applied, during the second exposure the job interview scenario is slightly adapted (Kirschbaum et al, 1995;Schommer et al, 2003;Petrowski et al, 2012) or replaced by a defensive speech in response to a false shoplifting accusation (Saab et al, 1989;Burleson et al, 2003). For the mental arithmetic subtask, most authors change the initial number of the serial subtraction task for the second exposure (Kirschbaum et al, 1995;Schommer et al, 2003;Petrowski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies have also shown smaller SBP responses in premenopausal women or women taking hormone replacement therapy, compared to postmenopausal women not taking hormone replacement therapy (e.g. Saab, Matthews, Stoney & McDonald, 1989;del Rio et al, 1998). Differences in diastolic blood pressure (DBP) responses have been less frequently observed.…”
mentioning
confidence: 99%